The dionysian in performance reclaiming the female transgressive performing body - Solomon, Zanne (Rhodes University, Faculty of Humanities, Department of Drama, 2012)
In this thesis I investigate the theoretical or philosophical notion/archetype of the Dionysian in relation to the transgressive female body in performance. I do so through 1) an investigation into the theories behind the Dionysian and the transgressive; 2) an examination of the performative practice of the transgressive female body; and 3) a personal exploration of the theatrical practice. 1) In the first chapter I introduce and thoroughly explore the archetypal concept of the Dionysian, and identify its significance because of its intrinsic association with the transgressive. I associate it with its oppositional force, the Apollonian, which is similarly significant because it is through the Dionysian disruption of the Apollonian from which the very notion of the transgressive springs. Through a review of Camille Paglia's seminal text on the subject of the DionysianÂ¹, this chapter provides a historical, mythological and theoretical context for the schism between the two archetypal aesthetics, starting from the description of the mythology of the ancient Greek gods, Dionysus and Apollo, and unpacks the transgressive nature of the Dionysian. Drawing on concurring theories of Friedrich Nietzsche and Julia Kristeva, as well as Hans Thies-Lehmann's writings on post-dramatic theatreÂ², Chapter One attempts to firmly establish the inherent link between the Dionysian and theatre and performance, as well as the Dionysian and the transgressive, and provide a thorough theoretical framework for the rest of the thesis. 2) The second chapter investigates the work of two female performance artistsÂ³ who (re)presentâ ´ their bodies as transgressive in performance, namely Marina Abramovic and Karen Finley. It critically examines specific performance works of theirs, and through this examination it explores how they (re)present their bodies as transgressive in performance, and why they do so. This chapter furthermore establishes the connection between the transgressive female performing body, as (re)presented by Abramovic and Finley, and the Dionysian. In so doing it explores how they negotiate this ancient aesthetic or practice in a contemporary performance context. I believe that these performance artists are in fact striving to celebrate and reclaim the Dionysian within their work, and I attempt to establish this within this chapter. 3) The third chapter of this thesis analyses my own practical exploration of the transgressive female body in performance in a piece entitled Bleeding Mermaid (2008). It examines this exploration in the context of the theory of the Dionysian, as well as investigating how and why I (re)presented my body as transgressive in the performance. The analysis furthermore questions how I understand my work on the (re)presentation of the transgressive female body in relation to, and within the context of, Finley and Abramovic's work on the same subject. Through this investigation, I aim to establish a link between the Dionysian and the transgressive female performing body; and investigate the motivation(s) behind the (re)presentation of the transgressive female body in performance. I hope to open up a pathway to the reclamation of the Dionysian, both in performance practice and research. Â¹Paglia, Camille. Sexual Personae: Art and Decadence from Nefertiti to Emily Dickinson. England: Penguin Books, 1990. Â²Lehmann, Hans-Thies. Postdramatic Theatre. Trans. and Intro. Karen Jürs-Munby. London and New York: Routledge, 2006. Â³Performance Art began around the 1960s in Europe and America. It is performance with a sense of immediacy "“ in that it is hard to replicate as it interacts with each unique audience "“ it is thus effectively a fresh/new experience each time. It breaks the boundaries of traditional theatre (form, structure, venue, time etc) and is often shocking or provocative in nature. It mixed the aesthetics of theatre and art, often taking place in installation settings. Performance Art has developed and morphed throughout the years, and is also referred to as Live Art in Britain. A performance artist is someone who produces performance art. It is possible that Performance Art no longer exists/is possible because it no longer shocks or affects the audience. â ´My use of the brackets in (re)presented/(re)present throughout this thesis is because I would like to make simultaneous reference to the words/connotations of "presentation" and "representation", without being bound to the connotations of illusion/falseness/non-reality as is associated with the word "representation" (in opposition to the concept of the "real"), and thus be left only with the one-dimensional approach/meaning of "presentation".
Keywords: Dionysia; Feminism and theater; Human body in literature; Performance art; Performing arts; Body image in women; Self-perception in women; Human body -- Social aspects